SELF-EFFICACY AND PROFESSIONAL COMMITMENT OF VOCATIONAL HIGH SCHOOL TEACHERS: A QUANTITATIVE SURVEY STUDY - Artono Artono; Ary Bayu Nugraha; Andi Hermawan (COMPASS: Journal of Education and Counselling, 2026)
This study aims to analyze the professional commitment of private Vocational High School (Sekolah Menengah Kejuruan/SMK) teachers in Depok City using a quantitative approach with a survey design. Teachers’ professional commitment is regarded as a crucial factor influencing instructional quality, professional sustainability, and vocational education performance. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, involving 40 private SMK teachers as respondents. Data analysis employed descriptive and inferential statistics to describe the level of professional commitment and examine the relationship between self-efficacy and teachers’ professional commitment. The results indicate that, overall, teachers demonstrate a high level of professional commitment, particularly in the affective dimension, normative commitment, and identification with professional values. Meanwhile, continuance commitment and professional recognition fall within the moderate category. These findings support the application of the Job Demands–Resources theory as well as Meyer and Allen’s three-component commitment model in the context of vocational education. This study provides practical implications for policy development and programs aimed at enhancing the professionalism of private vocational high school teachers.